EFEKTIVITAS HOT PLATE MODIFIKASI PADA PROSES ANALISIS COD (CHEMICAL OXYGEN DEMAND) - Pabbenteng; Elisabeth Alwina; Kissan; Zamrutdin (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Modification is changing the model, and shape of a tool without reducing the main function of the tool. The hot plate is laboratory equipment that can generally be used to transfer heat to a material/system. The principle is that heat from a heat source such as fire or electricity is transferred with an auxiliary material to the material or system that you want to raise the temperature. The hot plate is able to heat the sample above 100 ° C so that it can be used in the COD (Chemical Oxygen Demand) analysis process. The COD (Chemical Oxygen Demand) analysis process uses a modified hot plate circuit based on SNI 6989.15-2019. COD (Chemical Oxygen Demand) testing using a hot plate so far only heats 1 sample so it is wasteful in terms of economy. In this study, 1 hot plate was modified so that it could heat 3 to 4 test samples simultaneously, making it effective and economical and supporting government programs to save electricity. The error factor in sample analysis is reduced because the temperature of each sample tested is the same. The effective sample heating time is 2 hours with a temperature setting of 150oC, 200 °C , 250 oC because the replicate and triplicate treatments are green to red color changes